Luka Bakar, Jaringa, Ekstrak PERCEPATAN LEPASNYA JARINGAN NEKROTIK LUKA BAKAR PADA TIKUS PUTIH DENGAN PEMBERIAN EKSTRAK JINTAN HITAM: ACCELERATION OF FURNITURE OF FUEL WOVEN NECTROTIC NETWORK ON WHITE RATS WITH GIVING BLACK JINTAN EXTRACT - noviyanti, linda wieke (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2017)
Abstract The local response from burn wound is forming necrotic tissue. Black cumin seed is one of the natural substances that used to cure burn wound because it contains thymoquinone as antibiotic, antiinflammation, analgesic and antioksidant. This research is aimed to prove the effect of black cumin seed extract toward the lenght of necotic tissue extrication second degree burn wound in white rat Wistar strain. This study is experimental using 20 white rats as sample were devided into five groups, these were normal saline 0,9% group as control, silver groups, black cumin extract 50%, 75%, and 100% groups as experimental group. The measured variable in this research is length of necrotic tissue extrication which is measured by comparing the decrease rate of width of necrotic tissue. Result is black cumin seed extract 75% had the best effect toward rate of width of necrotic tissue second degree burn wound (p<0,001; ?=0,05). The conclusion was black cumin seed extract had an effect toward the length of necrotic tissue extrication second degree burn in white rat. Further study could be done to certainly identify the effect of turmeric extract toward healing process in 2 nd degree burn. Keywords: black cumin extract, second degree burn wound, length of necrotic tissue extrication